Pressure Injury Prevention and Management: A Gap Analysis Using Key Stakeholder Engagement. Issue 5 (September 2022) - Pittman, Joyce; Otts, Jo Ann; Riley, Bettina; Mulekar, Madhuri S.
Abstract : PURPOSE: The purpose of this study was to examine pressure injury prevention and management (PIPM) practices in an academic acute care setting. Specific aims were to (1) develop and examine key stakeholder engagement regarding PIPM practices, (2) develop a valid/reliable gap analysis instrument, and (3) conduct a gap analysis of current PIPM practices. DESIGN: Mixed-methods convergent design and participatory action research. SUBJECTS AND SETTING: A nurse-led council (Council) of key stakeholders from a large academic university healthcare setting was developed. The gap analysis was conducted in a southern gulf coast level I trauma academic acute care hospital in the Southeastern United States. METHODS: A multidisciplinary key stakeholder Council with 27 members was developed to accomplish study aims using the participatory action research approach to train, promote, and foster key stakeholder engagement in all aspects of the research process. The Pressure Injury Prevention Gap Analysis Instrument (PIPGAI) was developed and psychometrically tested. A gap analysis of PIPM practices across a level I trauma academic acute care hospital was conducted using the PIPGAI. RESULTS: The PIPGAI was developed using 2019 Pressure Ulcer/Injury Clinical Practice Guideline recommendations, an integrative literature review/appraisal, a concept map, and Council input. The overall PIPGAI content validity index of 0.95 demonstrated excellent content validity. The individual item content validity index scores ranged from 0.62 to1.0. Low-scoring items (0.62-0.75) were deleted or revised. Interrater reliability was demonstrated by percentage of agreement (62%-79%). Using a modified Delphi approach, items of disagreement were summarized and discussed until 100% consensus was achieved. A gap analysis of PIPM practices was conducted resulting in a cumulative score of 267/553 (48%), indicating gaps in PIPM practices. Fifty (73%) items had content present; 37 of 58 (64%) items had minimal detail, and 36 of 58 (62%) items were difficult or required notable effort to accomplish. Fifty items (63%) had a total score of 4 or less and were identified as a gap (range: 0-7). CONCLUSIONS: The main outcome of this study was an innovative and evidence-based gap analysis process. The study provides (1) a model for key stakeholder engagement, (2) a valid/reliable gap analysis instrument, and (3) a method to evaluate PIPM practices. Abstract :